Slowly Migrating Fracture Swarms in an Actively Serpentinizing Borehole - Aiken, John M.; Barras, Fabian; Renard, François; Hirth, Greg; Kelemen, Peter B.; Sohn, Robert A. (John Wiley and Sons Inc., 2026)
Peridotite rocks are primary targets for engineered geological carbon sequestration efforts because the carbon in (Formula presented.) -bearing fluids is transferred to the rock in the form of carbonate minerals during alteration reactions. Sequestration efforts must necessarily open fractures in the rocks surrounding a pumped borehole, but the current understanding of fracture growth during serpentinization of peridotite is limited to theoretical models and laboratory experiments on small samples. We deployed hydrophone arrays in peridotite boreholes established by the Oman Drilling Program and detected downward migrating fracture swarms that represent the first field observations of fracture growth in a serpentinizing rock. More than 2 years after the boreholes were established, we detected four, downward migrating tensile fracture swarms during an interval of elevated pore pressure following large rain events. All of the swarms occurred within a partially confined section of the local aquifer, beginning at a depth of (Formula presented.) 170 m and migrating to the bottom of the 400 m-deep hole at average rates of (Formula presented.) 6–20 cm. (Formula presented.). We demonstrate that pore fluid processes can explain both the triggering of the tensile fracture swarms and their slow migration rates. Our results indicate that the tip of fractures propagating away from the borehole maintained near-critical states over time such that relatively small increases in fluid pressure triggered tensile fracturing episodes, indicating that carbon sequestration efforts in mafic rocks should be able to open fractures and expose fresh rock to mineralization.
Keywords: CO2 sequestration; fracture mechanics; ophiolite; peridotite; reaction driven cracking; serpentinization; Geophysics; Geochemistry and Petrology; Earth and Planetary Sciences (miscellaneous); Space and Planetary Science